Transcolonoscopic spraying formalin solution for hemorrhagic radiation proctitis: a retrospective analysis - Huang, Kun; Zhao, Xiaolin; Yu, Jiufei; Cheng, Jianping; Wu, Lili (Frontiers in Medicine, 2024)
Background: Radiation proctitis is a common complication that occurs as a result of radiation therapy used to treat pelvic malignancies. The most common and bothersome symptom resulting from radiation proctitis is rectal bleeding, which can be persistent or recurrent. This study aimed to review our experience and evaluate the efficacy and safety of transcolonoscopic spraying of formalin solution in patients with hemorrhagic radiation proctitis.Methods: A total of 37 patients with hemorrhagic radiation proctitis, aged between 48 and 79 years (mean age 62.56±8.48 years), were divided into three cohorts based on the severity of radiation injury. Under direct endoscopic vision, a 4% formalin solution was applied directly to the rectal hemorrhagic mucosa. The patients were followed for a period of over 6 months after receiving treatment, during which the therapeutic effectiveness and occurrence of complications were observed.The study resulted in an overall response rate of 89.2% among all patients. The response rates for patients with grades 1-3 were 100%, 100%, and 66.7%, respectively. Notably, the rate of response among patients with grade 3 radiation injury was significantly lower compared to those with grades 1-2 (P=0.009).Mild adverse reactions, such as anal pain and tenesmus, were reported in a small number of patients but could be alleviated without any intervention.The endoscopic application of formalin solution for the treatment of hemorrhagic radiation proctitis has shown a significant effect, particularly in patients with grades 1-2 radiation injury. The observed effect is superior to that observed in patients with grade 3 radiation injury.